ZAKAT DEVELOPMENT: THE INDONESIA’S EXPERIENCE - Hafidhuddin, Didin; Beik, Irfan Syauqi (Al-Infaq: Jurnal Ekonomi Islam, 2010)
As the third pillar of Islam, zakat has very strategic role in the development of the ummah. Indonesia, being the most populous Muslim country, experiences rapid zakat development for the last decade. This could be observed from both collection and distribution sides of zakat, which indicate remarkable mprovement. However, Indonesia still faces a number of challenges including the wide gap between zakat potential and its actual collection. Hence, exchange of experience between Indonesia and other OIC member countries is highly needed.